Influence of functionalized and non-functionalized 2D graphene nanomaterial with organic phase change materials: Thermal performance comparison - Kalidasan B.; Pandey A.K.; Rajamony R.K.; Sharma K.; Fatehmulla A.; Buddhi D. (Elsevier B.V., 2025)
Thermal energy storage and harvesting using phase change materials (PCMs) is a crucial aspect of solar thermal utilisation and energy management. However, the intrinsic limitations associated with PCMs, such as their relatively lower thermal conductivity and sluggish thermal transport pose significant obstacles in the advancement of thermal energy harvesting and storage systems reliant on PCMs. Research explored by inclusion of nanomaterial with the PCM matrix is predominant depending on uniform diffusion and stability of the developed nanocomposite. In this research endeavour, we introduce a novel and synergistic approach to synthesis a functionalized graphene nanomaterials and compare its performance with non-functionalized graphene nanomaterial at various concentrations within organic PCMs, operating at a phase change temperature of 54 C. The formulated nanocomposite's thermophysical properties morphology, chemical stability, optical absorbance & transmittance, melting enthalpy, thermal stability and thermal reliability were investigated using sensitive instruments. The findings unveil a remarkable enhancement in thermal conductivity with functionalized graphene dispersed PCM exhibiting an astonishing surge of 106.7 % at a mere 0.8 wt% loading, when contrasted with conventional PCM. The optical transmittance of RT54-0.8fGr was significantly reduced from 56 % to 17.2 %, which enabled the effectiveness for solar thermal energy harnessing; meanwhile the melting enthalpy was energised to 193.4 J/g from 182.6 J/g. The developed nanocomposite with better optical property and melting enthalpy were tested for 500 numbers of accelerated thermal cycles and its chemical stability and thermal property were compared with PCM. Furthermore, a heat transfer analysis is numerically simulated to exhibit the thermal conductance performance of functionalized nanocomposite PCM over base PCM. The findings suggest that the functionalized graphene dispersed PCM matrix to exhibit highly favourable attributes for renewable thermal energy storage due to their exceptional comprehensive features. ? 2024